1987
DOI: 10.1021/ja00235a008
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS studies on the origin of high catalytic activity in nickel Y zeolite

Abstract: 52system. For DsL << DCuKTSM2 the lower limit for the translational diffusion coefficient for CuKTSM2 is equal to (60 -95) X lo-* cm2/s. Because the translational diffusion constant for 16-SASL at that temperature in DMPC is about 5 X the assumption that DsL Abstract: Nickel species contained in Y-type zeolite have been characterized by an EXAFS technique at each stage of catalyst preparation. When nickel ions were incorporated into the zeolite by aqueous ion exchange, a kind of "solution-like" hydrated state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 3 publications
(4 reference statements)
4
29
0
Order By: Relevance
“…The bond angles are close to octahedral: O′3-Ni1′2-O3′ ) 88°, O5-Ni1′2-O5 ) 79°, and O3′-Ni1′2-O5 ) 96°and 174°(again mean values). The presence of the Ni 4 O 4 unit shown in Figures 5 and 6 is supported by the EXAFS studies of Sano et al 7 and Dooryhee et al 14 who reported the presence of "oligomeric nickel oxides" in Ni-Y. 6,7 About each Ni 2+ ion, they found 3.0-3.5 oxygens at 2.08 or 2.02 Å and 3.0 Ni 2+ ions at 2.99 Å.…”
Section: Trigonal Ni 2+ Ions At the First Site I′supporting
confidence: 60%
See 2 more Smart Citations
“…The bond angles are close to octahedral: O′3-Ni1′2-O3′ ) 88°, O5-Ni1′2-O5 ) 79°, and O3′-Ni1′2-O5 ) 96°and 174°(again mean values). The presence of the Ni 4 O 4 unit shown in Figures 5 and 6 is supported by the EXAFS studies of Sano et al 7 and Dooryhee et al 14 who reported the presence of "oligomeric nickel oxides" in Ni-Y. 6,7 About each Ni 2+ ion, they found 3.0-3.5 oxygens at 2.08 or 2.02 Å and 3.0 Ni 2+ ions at 2.99 Å.…”
Section: Trigonal Ni 2+ Ions At the First Site I′supporting
confidence: 60%
“…7 Table 7). Additional H + ions, beyond the numbers given in Table 7, would be present if some of the water molecules that coordinate to Ni 2+ have dissociated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding spectra for metal oxides are given for comparison. The XANES pre-edge peak is attributed to the 1s-3d dipolar forbidden transition [21]. Principally, this 1s-3d forbidden transition gains additional intensity when the metal center is in a non-centrally symmetric environment through mixing of 3d and 4p orbitals caused by the breakdown of inversion symmetry due to the structure distortion.…”
Section: Resultsmentioning
confidence: 98%
“…Taking into account sites occupancies [3], a corrected Ni-O value of 2.16 Å was estimated [5]. This value is significantly higher than the Ni-O distances (from 1.87 to 2.05 Å ) determined for dehydrated samples by EXAFS (Extended X-ray Absorption Fine Structure) [5][6][7], the number of nearest oxygen neighbours being furthermore lower (between 3 and 4). These discrepancies prompted us to analyse precisely the evolution upon rehydration of the coordination shell around Ni 2+ in a NiNaX sample and this was made possible owing to the recent development of dispersive-EXAFS for the in situ study of catalytic materials, allowing the recording of complete absorption spectra in very short times [8,9].…”
Section: Introductionmentioning
confidence: 95%